EVALUASI ETIOLOGI KEJANG DEMAM DI RUMAH SAKIT UMUM HAJI MEDAN - ABDUL AZIS BIZLY; NUR CAHAYA (JURNAL ILMIAH SIMANTEK, 2021)
Fever that triggers seizures originates from the extracranial process. Viruses are the main cause of febrile seizures.Recent literature documents the presence of human herpes simplex virus 6 (HHSV-6) as an etiological agent in roseola inabout 20% of a group of patients who experience their first febrile seizures. Shigella gastroenteritis is also associated withfebrile seizures. To determine the etiology of fever in patients with febrile seizures from January 2019 to January 2020 atHaji General Hospital Medan. Descriptive cross sectional design. Patient febrile seizures patients are classified aspatients with etiolgy bacterial infection and viral infection. The research data were obtained from primary data form patientmedical records at the Hospital which included 51 patients and then analyzed using the univariat. Of the 51 children, 26 wereboys. Simplex febrile seizures were seen in 37 cases (72,5%). Most of the febrile seizures occurred in patients under 2 yearsold seen in 33 cases (64.7%). Viral infection were seen in 37 cases (72.5%). The most common comorbidities were upperresoiratory infection 25 cases (49%) and gastroenteritis 15 cases (29.4%).